Pendekatan Ilmu Ma‘ani terhadap Struktur Kalam dan Makna Tersirat dalam Surah Yusuf - Jauhar, Annisa Fitria Allicia (Study Program of Arabic Language Teaching, 2025)
This study explores the application of ilmu ma‘ani elements, such as kalam khabar, kalam insya’, qaṣr, al-faṣl wa al-waṣl, ījāz, iṭnāb, and Musāwah in selected verses of Surah Yusuf to uncover their rhetorical functions and implicit spiritual messages. This research employs a qualitative method with a library research design, focusing on linguistic structures and rhetorical expressions within the Qur’anic text. Primary data consists of verses from Surah Yusuf. In contrast, secondary data is derived from classical and contemporary tafsir (e.g., Tafsir Ibn Kathir, Tafsir al-Jalalayn, Tafsir al-Tahrir wa al-Tanwir) and relevant scholarly articles. Data were collected using documentation techniques and analyzed through content analysis, identifying rhetorical forms and interpreting their implied meanings through a balaghah framework. The findings conclude that the meticulous use of ilmu ma‘ani in Surah Yusuf exemplifies the Qur'an's linguistic miracle, where concise yet rich language effectively and efficiently delivers intricate spiritual and ethical messages, affirming its timeless relevance.